Peace, Youth, and Interfaith Leadership: Value-based Peacebuilding by Advancing Religious Peace Ideals - Goswami, Poojita; Walia, Rumit (International Journal of Advanced Research in Peace, Harmony and Education, 2024)
Religious intolerance in India is widening in the contemporary period, especially among the youth. The scope of enrooting a seed of peace in the community and promoting interfaith relations can be determined by enlightening the youth. The article aims to understand the role of the Global Peace Foundation in India in advancing youth through the training of interfaith leadership through its fifteen-day program. The study analyses the change from the perspective of the youth involved in the programme. It focuses on the abridgement of misconceptions when exposed to the values of the nine religions in the country. An acceptance of the practices and broader mindset in encompassing the values of all religions is observed by understanding interfaith relations and the peace and harmony they promote. An approach to value-based peacebuilding by the organisation is regarded as developing peace relations among different religions in India.